2016
DOI: 10.1038/srep36546
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach of utilization of the fungal conidia biomass to remove heavy metals from the aqueous solution through immobilization

Abstract: The biomass of filamentous fungi is an important cost-effective biomass for heavy metal biosorption. However, use of free fungal cells can cause difficulties in the separation of biomass from the effluent. In this study, we immobilized the living conidia of the heavy metal-resistant Penicillium janthinillum strain GXCR by polyvinyl alcohol (PVA)-sodium alginate (SA) beads to remove heavy metals from an aqueous solution containing a low concentration (70 mg/L) of Cu, Pb, and Cd. The PVA-SA-conidia beads showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…With the increase in BRB concentration from 10 to 50 mg/L, an increase in the adsorption capacity of ZnONP from 0.82 to 2.53 mg/g and a decrease in percentage adsorption from 82.1 to 50.6% was displayed. This trend is consistent with the ndings of other researchers 26,61,62 . Thus as the BRB concentration in the aqueous phase increased, more BRB molecules were xed on the active sites of ZnONPs, which resulted in site saturation, surface repulsions, and less percentage removal of dye from solution 63 .…”
Section: Brb Uptake On Znonpsupporting
confidence: 94%
“…With the increase in BRB concentration from 10 to 50 mg/L, an increase in the adsorption capacity of ZnONP from 0.82 to 2.53 mg/g and a decrease in percentage adsorption from 82.1 to 50.6% was displayed. This trend is consistent with the ndings of other researchers 26,61,62 . Thus as the BRB concentration in the aqueous phase increased, more BRB molecules were xed on the active sites of ZnONPs, which resulted in site saturation, surface repulsions, and less percentage removal of dye from solution 63 .…”
Section: Brb Uptake On Znonpsupporting
confidence: 94%
“… 18 20 . Among the microorganisms studied for metal ion biosorption (bacteria, yeasts, fungi and algae) 21 27 , the Candida species (sp.) is one of more popular microbes that have been explored and show satisfactory biosorption performance 28 – 32 .…”
Section: Introductionmentioning
confidence: 99%
“…secretes inorganic metabolic products such as sulphide, carbonate or phosphate ions in their respiratory metabolism which precipitate toxic metals (Cd) in a form of non-enzymatic detoxification. Fouvert and Roux [43] also studied the mycelial mat of Mucor niceri, A. niger and P. chrysogenum and reported their role in removal of nickel, zinc, cadmium and lead by bio-adsorption. Anand et al [44] also reported that T. viride scavenge Cu from the medium by binding with cell wall.…”
Section: Effect Of Heavy Metal and Scavenging Potential Of T Asperelmentioning
confidence: 99%